Relational and algebraic methods in computer science : 16th International Conference, RAMiCS 2017, Lyon, France, May 15-18, 2017, Proceedings /: 16th International Conference, RAMiCS 2017, Lyon, France, May 15-18, 2017, Proceedings. (2017) - Unknown
No abstract available